DAKWAH DALAM MEMBANGUN ETIKA KERUKUNAN HIDUP UMAT BERAGAMA - Jasmadi, Jasmadi (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2015)
Indonesia is multi-ethnics, culture and religions,require normative values to regulate social relations.Normative values on religion, social values and moresthat have been prevailing in the community, is thebasis for building a culture of inter-religious relations.Pancasila and the 1945‟s Constitution is a collectiveagreement in regulating the society and the state.National unity took place in the community where thevalues of religion has lived and practiced. Religiousdiversity has become a reality of history and they havebeen living side by side. Today, Da‟wah activities inbuilding awareness in the practice of religion amongthe other religious communities, is needed. Therefore,the practice of the “inclusive religion” should beapplied.